Improving Medical Students’ Learning Experience of Pathology by Online Practical Sessions through Virtual Microscopy - Safina Ahmed, Maryam Habib, Hania Naveed, Ghazala Mudassir, Mahwish Majid Bhatti, Rifat Nadeem Ahmad (Journal of Rawalpindi Medical College, 2022)
ABSTRACT: Objective: To assess the impact of interactive virtual pathology slides on students’ understanding of pathological disease processes. Materials & Methods: The study was conducted at Shifa College of medicine, Islamabad. Class of 3rd year MBBS, comprising of 111 students, was divided into two groups during two teaching modules. All students received online lectures prior to practical sessions. In the first module, one group was taught virtual slides through online interactive sessions, whereas the second group was taught same set of slides, using light microscopy and glass slides. Both groups were assessed at the end of the module by online test and their scores were compared. Similar exercise was repeated in the second module in which the control group became the test group to remove the selection bias. Questionnaire feedback was taken from students to get their perceptions. The results were compared by applying t-test and p-value was calculated. Results: The mean score of test group (group-1) in first module was 14.90 whereas mean score of control group (group-2) was 10.99. The t test was applied, and p-value calculated was significant (p=0.04). In the second module the groups were flipped. The mean score of test group (group-2) was 14.29 whereas control group (group-1) was 10.09. The p value was calculated which was again significant (p=0.04). The students gave their feedback through questionnaire. Conclusion: Overall, we believe that the use of virtual microscopy significantly improves student’s understanding of pathological lesions. Keywords: Education, medical, pathology, undergraduate, virtual microscopy.